The Effects of Exchange Rate Volatility on U.S. Forest Commodities Exports - Changyou Sun; Daowei Zhang (Forest Science, 2003)
This article addresses the impact of exchange rate volatility on U.S. exports of four forest commodities. Exchange rate volatility is measured by the standard deviation of the growth rate of real effective exchange rate of the U.S. dollar. The nonstationarity of individual time series is explicitly taken into account by employing multivariate cointegration analysis and error correction models. The results show that exchange rate volatility has a negative impact on U.S. exports in the long term, but short-term dynamics vary for different commodities. A stable currency policy in the long run helps promote U.S. exports of forest commodities, although some commodities may benefit from exchange rate volatility in the short term.